ผลของคลอไรด์ที่มีต่อการกำจัดซีโอดีในน้ำเสียปิโตรเคมีโดยใช้ระบบยูเอเอสบี - ณัฎฐริกา ตันติวงศ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
This research is to study effect of chloride on removal of COD in petrochemical wastewater using UASB system. The research was divided into 2 experiments. Both experiments using 3 identical UASB reactor. The first experiment used the petrochemical wastewater. It was prepared with varying COD ratios at 1,000, 1,500 and 2,000 mg/l, respectively. The second experiment used the petrochemical wastewater added with sodium chloride (NaCl) to maintain concentration at 600, 1,200 and 2,400 mg/l., respectively. The results of the first experiment with petrochemical wastewater of COD ratio at 1,000, 1,500 and 2,000 mg/l, it was found that COD removal efficiencies percentile 50 at steady state were 88.66, 90.49 and 89.58 %, respectively. The second experiment with petrochemical wastewater and sodium chloride (NaCl). It was found that COD removal efficiencies percentile 50 were 84.00, 89.44 and 86.54 %, respectively. The UASB system with COD ratios at 1,500 mg/l have the best performance in terms of removal for COD were 89.44 %. Scanning electron microscope observation of the sludge granule, it was start-up 2 experiments of sludge granule is not absolutely right. It have cavity in cell. Analysis of particle size distribution with D[subscript 50] and D[subscript 90] of COD concentration was kept constant at 1,500 mg/l have the greatly for the UASB system. From the result, it can conclude that the appearance of chloride effect on the efficiency of COD removal and sludge granule formation only during the period of system can adapt themselves which can be seen as the efficiency of COD removal of 3 reactors are closely. Furthermore, in the secand reactor, COD concentration is 1,500 mg/l, the size of sludge granule is the biggest and it is the most effection on COD removal so, it show that chloride is not effect on the efficiency of COD removal when operate system in long period.